Novel multiuser interference cancellation using simplex algorithm for CDMA systems - Zhiyong Bu; Haifeng Wang; Lilleberg, J.; Shixin Cheng (2000 IEEE International Conference on Personal Wireless Communications : Hyderabad, India, December 17-20, 2000, 2000)
A novel MAI-free multiuser receiver is proposed. A reference vector, which is different to the desired signals but creates the same multiple access interference, is generated. Thus the multiple access interference is regenerated by a new correlator and subtracted from the output of the conventional detector. The reference vector can be computed at a very low complexity cost by using the linear programming method (simplex algorithm). The simulation results show that the proposed scheme approaches the performance of the decorrelating detector but with much less complexity.